Understanding the scratch behaviour of polymeric materials with surface texture. (15th May 2018) - Gao, W.M.; Wang, L.; Coffey, J.K.; Daver, F.
Highlights: Scratching on polymeric components with surface textures is investigated with finite element method and scratch testing. A classification of scratches is proposed. Three parameters are developed for evaluating the irregular geometry of scratches on a surface texture. A new methodology for characterizing patterns and grains on polymeric materials is developed. Graphical abstract: Unlabelled Image Abstract: The surface texture of a polymeric product plays an important role in enhancing the product appearance and improving its resistance to scratch. The design and selection of texture features in the polymeric materials require an understanding of (i) the relationship between scratch/mar behaviour and the material property, (ii) the influence of surface texture on scratch resistance. This work simulates scratching processes on five different texture patterns at a number of scratch loads by using the coupled Eulerian-Lagrangian approach with the finite element method. To create texture pattern models for the simulations, a new methodology for characterizing the pattern and grain of textures was presented. To scale the scratch degree, three parameters were developed for the irregular geometry of scratches. The simulation results were compared with scratch experiments and a very good agreement between them was found. The analysis of the simulated scratches and the variation features of the three parameters led to a classification of scratches, which are bruise spots, creeping scratches and pattern damage, depending on the scratch load.